The Effect of Application of Typing Master Pro Version 11 Against Blind Ten-Finger Typing Ability - Qalby, Annur; Supriadi, Supriadi; Efriyanti, Liza; Khairuddin, Khairuddin (Education Achievement: Journal of Science and Research, 2024)
The purpose of this study is to assess the impact of the application of Typing Master Pro version 11 on students' typing skills in class XI of SMK Negeri 1 Ampek Angkek. This study was motivated by the low level of ability of class XI students majoring in Office Management and business services in typing ten fingers quickly and accurately, as well as the lack of utilization of applications supporting typing skills. The approach taken was to apply the Typing Master Pro version 11 application. This study used a quasi-experimental method with a quantitative approach. The data instrument used involved a test. The results showed an increase in students' ten-finger typing skills. The experimental group experienced an increase in typing skill scores of 71.17%, achieved a completeness rate of 87.5%, and an accuracy rate of 90%. Meanwhile, the control group experienced an increase of 37.22%, with a completion rate of 43.75%, and an accuracy rate of 80%. The increase in the control group was smaller than the increase in the experimental group.